FOOD AND NUTRIENT INTAKE AMONG ADULT OF ISFAHAN, IRAN - N. Mohammadifard; N. Sarrafzadegafl; A. Jalali; H. Alikhassi; M. Rafie; F. Sajadi; M. Boshtani; S. Mirlohian (Tehran University of Medical Sciences, 2000)
Many common diseases, including cardiovascular disease (CVD) are associated with diet. Hyperlipidemia, hypertension, diabetes and obesity are major risk factors for CVD which are diet-related and the incidence of which is on the increase in Isfahan, Iran. This cross-sectional descriptive study was conducted, using the 24-hour recall questionnaire, to determine dietary pattern of the adult (>19 years old) population of Isfahan. Based on 2 pilot studies 1200 randomly selected individual were included in the study; equal proportions of both sexes in the age range 19-51 + years old were selected. Data were collected in all the 4 season of the year, 30 days in each season. Data were collected through interviews, using the 24-hour recall questionnaire and a picture book let of food items consumed. Analysis of the data was done using t.student and chi square test in SPSS software. The results were as follows: The mean daily energy was 2070 kcal, the proportion of energy derived from fat, protein and carbohydrate being 23.2%, 12, 4% and 63.0%, respectively; the mean daily cholesterol intake was 255 mg/day. An intersectoral intervention programme is being planned aiming at correcting the dietary habits of Isfahan population.